1992
DOI: 10.1126/science.1553546
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Incorporation of Novel Backbone Structures into Proteins

Abstract: A number of unnatural amino acids and amino acid analogs with modified backbone structures were substituted for alanine-82 in T4 lysozyme. Replacements included alpha,alpha-disubstituted amino acids, N-alkyl amino acids, and lactic acid, an isoelectronic analog of alanine. The effects of these electronic and structural perturbations on the stability of T4 lysozyme were determined. The relatively broad substrate specificity of the Escherichia coli protein biosynthetic machinery suggests that a wide range of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
162
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 27 publications
3
162
0
2
Order By: Relevance
“…During continuous translation, however, P site-bound peptidyl-D-aa-tRNAs partition ECs into two subpopulations, a productive subpopulation that is competent for further rounds of translation elongation and a nonproductive subpopulation that is translationally arrested. This arrested subpopulation, which results in truncated polypeptide products containing a D-amino acid at their C termini due to the failure of the P site-bound peptidyl-D-aa-tRNA to act as a peptidyl-transferase donor, provides the most likely explanation for the poor unnatural amino acid incorporation efficiencies that have been observed during attempts to synthesize proteins containing D-Tyr (8), D-Trp (14), D-Arg (14), and possibly other unnatural amino acids (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During continuous translation, however, P site-bound peptidyl-D-aa-tRNAs partition ECs into two subpopulations, a productive subpopulation that is competent for further rounds of translation elongation and a nonproductive subpopulation that is translationally arrested. This arrested subpopulation, which results in truncated polypeptide products containing a D-amino acid at their C termini due to the failure of the P site-bound peptidyl-D-aa-tRNA to act as a peptidyl-transferase donor, provides the most likely explanation for the poor unnatural amino acid incorporation efficiencies that have been observed during attempts to synthesize proteins containing D-Tyr (8), D-Trp (14), D-Arg (14), and possibly other unnatural amino acids (5).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies with these same aa-tRNAs demonstrated that D-Tyr-tRNA Tyr bound more weakly to elongation factor (EF) Tu than L-Tyr-tRNA Tyr and that D-Tyr was incorporated into the nascent polypeptide by the ribosome at a slower rate and with a lower yield than L-Tyr (13). More recent studies have used engineered suppressor tRNAs (i.e., in vitro transcribed tRNAs lacking all posttranscriptional modifications that read through stop or sense codons) and have reported D-amino acid incorporation efficiencies ranging from 0% to greater than 40% (4,5,14,15), depending on the in vitro translation system used (i.e., comprised of a cell extract or of fully purified components), the identities of the engineered tRNA and D-amino acid used, and the inclusion or exclusion of DTD.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a method was described that allowed the introduction of noncoded amino acids by introducing a stop codon. It used a modified tRNA that is acylated with the unnatural amino acid and has a recognition site complementary to the stop codon (Ellman et al, 1992). Another approach is the replacement of peptide fragments in a protein with the help of proteases (Chaiken, 1981).…”
Section: Discussionmentioning
confidence: 99%